Newspaper discourse: Constructing representations of terrorist groups (IRA and ISIS) - Gabriella Louise Julia Holt (Fields, 2022)
Terrorism is a phenomenon which is constantly transforming and evolving, resulting in a plethora of research aiming to better understand it. More recently, as media has become globalised, there has been a surge of research into the relationship between terrorism and the media. However, there is a lack of studies comparing media representations of terrorist groups from two separate eras and ‘waves of terrorism’ (Rapoport, 2013). This research aims to fill this gap by examining the discourse used in newspapers to construct representations of the Irish Republican Army (IRA) and Islamic State of Iraq and Syria (ISIS). This research used a qualitative methodology, discourse analysis to look at words and their meaning. Data was collected, for the analysis from both The Guardian and the Daily Mail newspapers. The articles were analysed using NVIVO. Differences were identified in the discourse used to represent terrorist groups in 2017 from those used in 1975. In 2017, newspapers were more likely to label the perpetrators as ‘sick’ and the attack as a ‘terrorist’ attack, discussing the victim’s injuries using more violent terminology. While 1975 newspapers were more likely to comment on political reasoning and ideology. An increased presence of sensationalisation, in the 2017 newspapers, seems to suggest a possible shift towards sensationalising terrorist events. More research is now needed on a larger scale, to consider if these changes in discourse occur more widely, and to examine what impact they have on public perception.